The effectiveness of proanthocyanidins cacao pods (theobroma cacao l) on increasing socket epithelial thickness post toothextraction in wistar rats - Yani C. Rahayu; Budi Yuwono; Alifia Wandansari (Journal of Dentomaxillofacial Science, 2020)
Objective: The aim of this study was examine theeffectivenessof proanthocyanidins cacaopods (Theobroma cacao L) extract on increasing socketepithelialthicknessposttooth extractionin Wistar Rats. Proanthocyanidins has benefis as antiinflammation, antioxidant and antibacteria agent. Post-extraction wound can cause complication, which can make long the healing process. This is where anti-inflammatory is needed to prevent infection, so that it can avoid bacterial contamination and can shorten the inflammatory process. Material and Methods:These study was an experimental laboratory research on thickness of socket epithelium of Wistar rats given proanthocyanidins cacao pod extract post extraction. A total of 24 male Wistar rats was divided into 3 group; which was treated with 100 mg/ml proanthocyanidins cocoa pod extract as treatment group, distilled placebo gel as negative control group and alvogyl as positive control group. On day 7 and day 14 the sampel was sacrified and tissue processing was made. The gingival epithelial thickness was determined by software image raster on light microscopy. Results:Analysisof One way Anova showed there was a significant difference0.001 between groups. The epithelium oftreatment group, was thicker than the control group significantly.Conclusion:Proanthocyanidins cocoa pods (Theobroma cacao L)  extract effectiveincreasing the thickness of socket epithelium postextraction in Wistar rats.